Factors affecting the improvement of mango plantation for commercial ripe fruit production and SWOT analysis of Nam Dok Mai Mango collaborative farming in Bang Phli District, Samut Prakan Province, Thailand Short Communications - Khermkhan, J.; Chepoo, K.; Lertdanaipong, E. (My University, 2020)
The factors affecting the improvement of mango plantation for commercial ripe mango production and SWOT analysis in Bang Phli District, Samut Prakan Province, Thailand was investigated. The results showed that age and education were factors affecting the improvement of mango var Num Dok Mai for commercial ripe mango production. Farmers ages 31-50 years old had upper senior high school level of education. The result of SWOT analysis showed that the farmers grew mangoes for ripening. Their strengths include good soil quality, flawless mango skin and thus received GAP-free standards. In addition, they had opportunities due to high market demand and support from the government. However, their weak points were lack of labour because most of the farmers were elderly and uncertainty in productivity. They were threatened with worms, insects, diseases, climate changes and stealing.
Keywords: Collaborative farm; Nam Dok Mai Mango; Production behavior; SWOT analysis